Bisphosphonate inhibitors of squalene synthase protect cells against cholesterol‐dependent cytolysins. Issue 6 (15th May 2021) - Pospiech, Mateusz; Owens, Siân E.; Miller, David J.; Austin‐Muttitt, Karl; Mullins, Jonathan G. L.; Cronin, James G.; Allemann, Rudolf K.; Sheldon, I. Martin
Abstract: Certain species of pathogenic bacteria damage tissues by secreting cholesterol‐dependent cytolysins, which form pores in the plasma membranes of animal cells. However, reducing cholesterol protects cells against these cytolysins. As the first committed step of cholesterol biosynthesis is catalyzed by squalene synthase, we explored whether inhibiting this enzyme protected cells against cholesterol‐dependent cytolysins. We first synthesized 22 different nitrogen‐containing bisphosphonate molecules that were designed to inhibit squalene synthase. Squalene synthase inhibition was quantified using a cell‐free enzyme assay, and validated by computer modeling of bisphosphonate molecules binding to squalene synthase. The bisphosphonates were then screened for their ability to protect HeLa cells against the damage caused by the cholesterol‐dependent cytolysin, pyolysin. The most effective bisphosphonate reduced pyolysin‐induced leakage of lactate dehydrogenase into cell supernatants by >80%, and reduced pyolysin‐induced cytolysis from >75% to <25%. In addition, this bisphosphonate reduced pyolysin‐induced leakage of potassium from cells, limited changes in the cytoskeleton, prevented mitogen‐activated protein kinases cell stress responses, and reduced cellular cholesterol. The bisphosphonate also protected cells against another cholesterol‐dependent cytolysin, streptolysin O, and protected lung epithelial cells and primary dermal fibroblasts against cytolysis. Our findings imply that treatment with bisphosphonates that inhibit squalene synthase might help protect tissues against pathogenic bacteria that secrete cholesterol‐dependent cytolysins.